Enhancement of Enzymatic Saccharification of Poplar by Green Liquor Pretreatment - Xin Meng; Wenhui Geng; Hao Ren; Yongcan Jin;; Hou-min Chang; Hasan Jameel (BioResources, 2014)
Green liquor (Na2S + Na2CO3, GL) pretreatment is an effective pathway for improving the enzymatic digestibility of lignocellulosic biomass for the production of bioethanol. In this work, GL was employed as a pretreatment to enhance the enzymatic saccharification of poplar. During pretreatment, the increase of H-factor and TTA charge resulted in enhanced delignification and increased degradation of polysaccharides. The sugar yield of enzymatic hydrolysis increased rapidly with increasing TTA charge in GL pretreatment, while the effect of different H-factors (from 400 to 800) on sugar yield was unnoticeable. The pretreated solid recovery was 75.5% at a lignin removal rate of 29.2% under optimized conditions of total titratable alkali (TTA) charge 20%, sulfidity 25%, and H-factor 400. The sugar yield of glucan, xylan, and total sugar of GL-pretreated poplar in enzymatic hydrolysis reached up to 89.9%, 65.5%, and 82.8%, respectively, at a cellulase loading of 40 FPU/g-cellulose.